2013
DOI: 10.1177/0192513x13481776
|View full text |Cite
|
Sign up to set email alerts
|

Heightened Maternal Separation Anxiety in the Postpartum

Abstract: Maternal separation anxiety (MSA) refers to feelings of anxiety elicited in a mother during separation from her infant. The role of social and structural disadvantage in the etiology of high MSA has been overlooked. Secondary analysis of data from the Longitudinal Study of Australian Children (N = 3,897) revealed that compared to socioeconomically advantaged women, women of low socioeconomic position had a fourfold increased odds of reporting high (>80th percentile) MSA (odds ratio = 4.37, 95% confidence inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Parents have described the negative emotions they experience with departures from the NU, and NU nurses have observed these as well [79,80]. Moderate distress upon separation is considered normal and desirable, and an indicator of secure attachment, and studies have found that mothers of infants who have health problems may be more likely to report significant separation anxiety [81,82].…”
Section: Discussionmentioning
confidence: 99%
“…Parents have described the negative emotions they experience with departures from the NU, and NU nurses have observed these as well [79,80]. Moderate distress upon separation is considered normal and desirable, and an indicator of secure attachment, and studies have found that mothers of infants who have health problems may be more likely to report significant separation anxiety [81,82].…”
Section: Discussionmentioning
confidence: 99%
“…With child care available, participants reported feeling distrustful or anxious about leaving their children with others. Indeed, low-income women are more likely to report high maternal separation anxiety than are higher-income women (Cooklin et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Maternal history of mood disorder predisposes women to heightened risk of worse mood in the postpartum including difficulties with adjustment (beyondblue, 2011; Leigh & Milgrom, 2008), which may include more difficulties in negotiating separation from their infant. Single mothers, those who are experiencing financial hardship, or are living in conditions associated with socioeconomic disadvantage may be more concerned, anxious, and protective of their children than mothers with better access to support, resources, or higher quality care for their children (Cooklin et al, 2013). Finally, maternal employment participation in the postpartum requires regular motherϪinfant separations and is associated with lower separation anxiety in the postpartum (Cooklin et al, 2013(Cooklin et al, , 2012DeMeis, Hock, & McBride, 1986;Hock & DeMeis, 1990;Hsu, 2004).…”
Section: Effects Of Maternal Separation Anxiety On Parenting and Chil...mentioning
confidence: 99%
“…Single mothers, those who are experiencing financial hardship, or are living in conditions associated with socioeconomic disadvantage may be more concerned, anxious, and protective of their children than mothers with better access to support, resources, or higher quality care for their children (Cooklin et al, 2013). Finally, maternal employment participation in the postpartum requires regular motherϪinfant separations and is associated with lower separation anxiety in the postpartum (Cooklin et al, 2013(Cooklin et al, , 2012DeMeis, Hock, & McBride, 1986;Hock & DeMeis, 1990;Hsu, 2004). A third aim of the study was to ascertain whether the strength and pattern of the relationships between postnatal maternal separation anxiety and psychological distress, and overprotective parenting and socioemotional outcomes for children in toddlerhood is moderated by these child (gender, first-born) and maternal/family characteristics (history of depression, family structure, socioeconomic position, and employment status).…”
Section: Effects Of Maternal Separation Anxiety On Parenting and Chil...mentioning
confidence: 99%